5.THE EFFICACY AND SAFETY OF PERCUTANEOUS NEPHROLITHOTOMY IN CORRELATION WITH DIFFERENT RENAL STONE BURDENS (Iraqi Journal of Medical Sciences, 2019)
Background: The improvements in instruments and technique of percutaneous nephrolithotomy (PCNL) in the last 3 decades have led to expansion in its indications to include even the large and complex renal stone cases.Objective: To determine the efficacy and safety of PCNL in relation to stone complexity.Methods: In this prospective, clinical, interventional study, 51 patients with symptomatic renal stones of different sizes and locations, were admitted in our Urology Unit, fully evaluated and treated by our team with PCNL. For all the patient’s data collected were: age, gender, body mass index (BMI), previous renal surgery, pre-operative stone number, stone size, stone position, stone opacity, surgical approach, operative time, stone clearance rate, postoperative residual stones and complications, hospital stay and adjuvant therapy. By using different statistical methods, correlations were made to elicit the impact of stone size, stone position, stone opacity, BMI and previous renal surgery, operative time, stone free rate, complication rate and the need for auxiliary procedures.Results: In this study, the 51 included patients were 31 males and 20 females with a mean age 40.3 year. All the stones treated were over 2 cm in their longest diameter, with 58.8% of them were ? 3 cm, and mean stone size was 4.2±0.99 cm. The most prevalent site of stone was the lower calyx (39.2%), followed by (37.3%) as partial staghorn, while complete staghorn calculi constituted (11.8%). The final success rate of treatment was 86.3%. (60.8%) of the cases found to be stone free at immediate postoperative period. Auxiliary procedures were used in (27.5%) patients, to improve the stone clearance. Residual stones were ultimately remained in only (7.8%). Complications occurred in 11 patients (21.6 %).Conclusion: PCNL though demanding, is an effective and reasonably safe procedure for the treatment of different renal stone burdens. Size and position of stones in the calyceal system and past renal surgery were the main determinants of operative time, stone clearance, complication rate and the need for auxiliary procedures.Keywords: Renal stone, PCNL, stone complexity, stone free rate, complicationsCitation: Al-Azzawi IS, Mohammed Zaki AW, Jwaid HI, Salih SL, Al-Obaidi AA. The efficacy and safety of percutaneous nephrolithotomy in correlation with different renal stone burdens. Iraqi JMS. 2018; 16(4): 385-392. doi: 10.22578/IJMS.16.4.5
Keywords: Renal stone; PCNL; stone complexity; stone free rate; complications